Laboratory tests and diagnostic procedures - Chernecky, Cynthia C; Berger, Barbara J (Saunders, 2013)
Find complete answers to questions such as which laboratory tests to order or what the results might mean. Laboratory Tests and Diagnostic Procedures, 6th Edition covers more tests than any other reference of its kind, with over 900 lab tests and diagnostic procedures in all. In Part I, you'll find an alphabetical list of hundreds of diseases, conditions, and symptoms, including the tests and procedures most commonly used to confirm or rule out a suspected diagnosis. In Part II, you'll find descriptions of virtually every laboratory and diagnostic test available. This edition is updated with the latest research and over 20 NEW test entries. Written by educator Cynthia Chernecky and clinical nurse specialist Barbara Berger, this lab reference covers today's lab tests with concise, easy-to-use information.